PERANCANGAN SISTEM PENJUALAN DALAM RANGKA MENINGKATKAN KETERTAGIHAN PIUTANG PADA USAHA PERCETAKAN DI SURABAYA - LYDIAWATI UTOMO, SHIERLY (Universitas Katolik Widya Mandala Surabaya, 2012)
Sales System is one of the cycles that are important in supporting the business processes of an enterprise especially in generating revenue but unavoidable problems often occur at the company in the field in its sales system. This type of research conducted in the form of case studies at a printing company in Surabaya on the analysis of sales and payment system issues and alternative receivables solutions to resolve problems at the company. Structuring an invoice that is not good, yet the implementation of authorization policies granting credit to customers, less complete financial statements, and corporate developments that lead to the expansion of business into the problems that lead to ineffective sales system that resulted in the billing system and customer receivables. Based on the above problems it is necessary to improve sales and payment systems are computerized and use the database at the printing company. Improvement begins with analyzing system problems occurred, then fix a flowchart and DFD sales and payment systems, access systems design, designing ERD and end with the physical design of system design.